1999
DOI: 10.4269/ajtmh.1999.60.521
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled field trial to determine the efficacy and safety of Malarone (atovaquone/proguanil) for the prophylaxis of malaria in Zambia.

Abstract: Abstract. Malaria poses a major health risk to people who are exposed to infection in malaria-endemic areas. A randomized, double-blind, placebo-controlled study was conducted to determine the efficacy and safety of Malarone (250 mg of atovaquone/100 mg of proguanil hydrochloride per tablet) for the chemoprophylaxis of Plasmodium falciparum malaria in Zambia. Adult volunteers received a three-day treatment course of Malarone to eliminate pre-existing parasitemia and were then immediately randomized to treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 21 publications
0
43
0
2
Order By: Relevance
“…When A-P is taken for chemoprophylaxis for malaria, gastrointestinal side effects and headache predominate (49,74,92,114,125). In studies of the treatment of malaria with higher doses of A-P, elevations of liver transaminase and bilirubin levels are recorded in approximately 15% of treated patients (77,79).…”
Section: Pharmacokinetics and Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…When A-P is taken for chemoprophylaxis for malaria, gastrointestinal side effects and headache predominate (49,74,92,114,125). In studies of the treatment of malaria with higher doses of A-P, elevations of liver transaminase and bilirubin levels are recorded in approximately 15% of treated patients (77,79).…”
Section: Pharmacokinetics and Side Effectsmentioning
confidence: 99%
“…In randomized, placebo-controlled trials, A-P demonstrated Ͼ95% protective efficacy in semi-immune adults in Kenya (113) and Zambia (125) and in children in Gabon (74).…”
Section: Review Of Clinical Trialsmentioning
confidence: 99%
“…ATQ drug concentrations may be lower if used prophylactically for prevention (10). For example, in a randomized controlled trial in which 250 mg ATQ was administered with 100 mg proguanil hydrochloride to healthy volunteers once daily, trough ATQ concentrations were 2000 ng/mL after up to 10 weeks of treatment (18). Thus, based on dosing characteristics, the low or high ATQ assay may be selected for drug quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Atovaquone/proquanal has demonstrated efficacy for malaria prophylaxis in areas with predominantly P. vivax (Soto et al, 2006). Atovaquone/proguanil's suppressive prophylaxis effectiveness has been shown in several clinical trials, three of which were among semi-immune populations in Gabon, Kenya, and Zambia and conducted as double-blinded, randomized, and placebo controlled trials, where overall efficacy of 98% in preventing malaria was observed in this population (Lell et al, 1998;Shanks et al, 1998;Sukwa et al, 1999;Kain et al, 2001). In two other large studies, in which non-immune travelers to malaria endemic regions were randomized to receive atovaquone/proguanil, mefloquine, or chloroquine plus proguanil, none of the patients in the atovaquone/proguanil arms who completed the study developed malaria (Hogh et al, 2000;Overbosch et al, 2001).…”
Section: Atovaquone and Proguanil Hydrochloridementioning
confidence: 99%